(untitled) (Bangladesh Critical Care Journal, 2019)
Background: Gastric polyps are small gastric mucosal lesions, usually asymptomatic in most cases and are generallydiscovered incidentally during upper Gastro Intestinal (GI) tract endoscopy. But some polyps have malignant potential.We observed the characteristics and frequency of gastric polyps, derived from the gastric mucosal epithelium in a seriesof endoscopies. Method: Fifty three patients were studied in a series of 2890 consecutive upper GI endoscopies done over one yearperiod. Each patient had only one examination and were analyzed on the basis of their location, size, type and histopathological findings. All patients had at least one gastric polyp, as confirmed by histological examination. Result: Among 2890 endoscopies we found gastric polyps in 53 cases. So the incidence was 1.83 %. Mean age of thestudy population was 50.25±11.75. Polyp was more prevalent among female (64%). Most of the patients were presentedwith anemia, heartburn and abdominal pain, 57%, 42% and 36% respectively. Other less common clinical features areanorexia (13%), melaena (9.4%) and hematemesis (1.9%). 64% patients were diabetic and 76% patients used PPI withduration of 19.00±9.78 months.Most of the polyps were located at the body of stomach (47.1%), less common sites were antrum (15.1%), cardia(7.6%), fundus (7.6%), Gastro Esophageal (GE) junction (3.8%) and duodenum (1.9%). Majority of the polyps weresmall and medium sized (37.7%, 35.8%) and large (11.3%). Sessile polyp was found in 49.1% cases, other common typewas pedunculated (39.5%). Only 28% patient had surface ulceration on polyp and commonest histological type washyperplastic 75.4%, 18.9% patient had adenomatous polyp. Brunner’s gland adenoma and carcinoid were rare, 3.8%and 1.9% respectively. Multiple polyps were found in 30% patient. Conclusion: Gastric epithelial polyps are infrequent and most of them measure less than 1 cm. The upper GI tractendoscopy is the safest and efficient method for the diagnosis of the gastric polyps, as in most of the patients does notshow characteristic symptoms. The histopathological definition is necessary to classify the polyps as well as detectionof dysplastic changes. Biopsy from different part of the stomach is necessary to find out the gastritis and dysplasticchanges. Bangladesh Crit Care J September 2019; 7(2): 90-94